2023
DOI: 10.1007/s11109-022-09852-9
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Mental Health Problems in Childhood and Adult Voting Behaviour: Evidence from the 1970s British Cohort Study

Abstract: The link between childhood mental health difficulties such as conduct problems and adult political abstention has been overlooked despite early mental health difficulties potentially resulting in political self-marginalisation. Using the1970s British Cohort Study, we estimate developmental trajectories of conduct problems (i.e., from 5 to 16 years). Logistic regression, linear probability models, and propensity score matching were then conducted to test the association between trajectory group membership and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…However, the co-occurrence of MH conditions and heterotypic continuity, as well as the spectrum of MH conditions investigated currently remains understudied in the literature on MH and political outcomes, warranting more attention. In the context of the current findings, coupled with recent findings linking childhood and adolescent conduct problems to reduced voter turnout in mid-adulthood (Girard & Okolikj, 2023), we would argue that it is crucial for future research to take a lifespan approach when investigating the psychological origins/antecedents of political outcomes, rather than focusing almost exclusively on adults.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…However, the co-occurrence of MH conditions and heterotypic continuity, as well as the spectrum of MH conditions investigated currently remains understudied in the literature on MH and political outcomes, warranting more attention. In the context of the current findings, coupled with recent findings linking childhood and adolescent conduct problems to reduced voter turnout in mid-adulthood (Girard & Okolikj, 2023), we would argue that it is crucial for future research to take a lifespan approach when investigating the psychological origins/antecedents of political outcomes, rather than focusing almost exclusively on adults.…”
Section: Discussionmentioning
confidence: 74%
“…At the same time, adolescence is also a formidable time for the development and emergence of voting habits, political ideology, and activism (Okolikj and Hooghe 2022;Pancer et al 2007), which evidence stability over time (Franklin 2004). And yet, the literature examining the association between MH and political participation often overlooks this developmental period, with some notable exceptions (e.g., Girard & Okolikj, 2023;Wray-Lake et al, 2019). Against this backdrop, our results then contribute in novel ways to the emerging literature on the intersection between MH and political outcomes, pointing to 1) the importance of late childhood/early adolescence and 2) the nuanced complexity of associations which are dependent on the type of MH difficulty present, co-occurrence of MH difficulties, and the political outcome considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be important for future research to examine the association between mental health and voting using measures that have been validated in all of our study countries. In addition, in the current study the analysis was only adjusted for factors occurring in adulthood (as no information was collected on childhood characteristics) even though one recent study found that childhood conduct problems were also associated with decreased voting in adulthood even after controlling for adult psychiatric morbidity 70 . This suggests that it may be necessary for future studies to focus on both internalising and externalising problems when examining voting behaviour, and also, that the use of a life course perspective would be of value.…”
Section: Discussionmentioning
confidence: 99%